Integration of PID-MRAC and Novel GCC-C2C for Developing Adaptive Deterministic MPPT - Nurcahyo, Sidik; Suyono, Hadi; Hasanah, Rini Nur; Muslim, Muhammad Aziz (Universitas Muhammadiyah Yogyakarta, 2025)
This article proposes a new photovoltaic (PV) Maximum Power Point Tracker (MPPT) using PID-MRAC with a novel tracker of Gradual Capacitor-Charging (GCC) and Capacitor-to-Capacitor charge transfer (C2C). The research contribution is omitting the power fluctuation of optimisation-based MPPT and discontinuity or power loss of I-V sweep-based MPPT. GCC regularly and deterministically locates the maximum PV power voltage (Vmpp) by connecting a parallel capacitor to PV only when the PV is isolated from the converter. If one cycle of I-V sweeping is completed, C2C empties the capacitor by transferring its charge to a power supply capacitor to avoid the power-loss problem. A PID and non-inverting buck–boost converter was assigned to regulate the PV output voltage (Vpv) at Vmpp, thus enabling maximum energy harvesting. The Model Reference Adaptive Control (MRAC) adjusts the PID parameters to maintain the MPPT performance. Simulation results show that the MPPT worked well against load and irradiance changes, Iph=2.0A for 0.6s and Iph=3.8A for 1.4s. The GCC-C2C successfully locates Vmpp within 410ms. The PID could regulate Vpv to Vmpp with a settling time of 200ms at the initial stage or less than 10ms at the next stages. The MRAC also successfully tuned the PID parameters during operation. The superiority of this method over the P&O MPPT is its capability to deliver more power at various load power rates. Harvesting efficiency of the proposed MPPT at 5 ohm and 50 ohm loads is 96% and 82%, respectively, while P&O is only 84% and 21%.